Examining the interseasonal resurgence of respiratory syncytial virus in Western Australia. Issue 3 (25th August 2021) - Foley, David Anthony; Phuong, Linny Kimly; Peplinski, Joseph; Lim, Selina Mei; Lee, Wei Hao; Farhat, Asifa; Minney-Smith, Cara A; Martin, Andrew C; Mace, Ariel O; Sikazwe, Chisha T; Le, Huong; Levy, Avram; et al.
Abstract : Background: Following a relative absence in winter 2020, a large resurgence of respiratory syncytial virus (RSV) detections occurred during the 2020/2021 summer in Western Australia. This seasonal shift was linked to SARS-CoV-2 public health measures. We examine the epidemiology and RSV testing of respiratory-coded admissions, and compare clinical phenotype of RSV-positive admissions between 2019 and 2020. Method: At a single tertiary paediatric centre, International Classification of Diseases, 10th edition Australian Modification-coded respiratory admissions longer than 12 hours were combined with laboratory data from 1 January 2019 to 31 December 2020. Data were grouped into bronchiolitis, other acute lower respiratory infection (OALRI) and wheeze, to assess RSV testing practices. For RSV-positive admissions, demographics and clinical features were compared between 2019 and 2020. Results: RSV-positive admissions peaked in early summer 2020, following an absent winter season. Testing was higher in 2020: bronchiolitis, 94.8% vs 89.2% (p=0.01); OALRI, 88.6% vs 82.6% (p=0.02); and wheeze, 62.8% vs 25.5% (p<0.001). The 2020 peak month, December, contributed almost 75% of RSV-positive admissions, 2.5 times the 2019 peak. The median age in 2020 was twice that observed in 2019 (16.4 vs 8.1 months, p<0.001). The proportion of RSV-positive OALRI admissions was greater in 2020 (32.6% vs 24.9%, p=0.01). There were no clinically meaningful differences in length of stay or disease severity. Interpretation: The 2020 RSV season was in summer, with a larger than expected peak. There was an increase in RSV-positive non-bronchiolitis admissions, consistent with infection in older RSV-naïve children. This resurgence raises concern for regions experiencing longer and more stringent SARS-CoV-2 public health measures. Abstract : Lockdowns associated with the COVID-19 pandemic have led to an unusual epidemiology for common childhood respiratory pathogens. In this paper, the epidemiology and clinical characteristics of summertime RSV infection in Western Australia are described.